IMPLEMENTASI GREEN PRACTICES PADA CAFÉ NYEDUH KOPI DI KECAMATAN PENEBEL KABUPATEN TABANAN PROVINSI BALI - I Made Krisna Surya Dharma; Putu Indah Rahmawati; A A Ngurah Yudha Martin Mahardika (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the increasing need to implement green practices in local culinary businesses in Bali. The main problems are resource management, business concepts, and unequal environmental awareness. This study aims to describe the factors managers consider in developing businesses, the concept of culinary development based on local potential, and the implementation of green practices at Café Nyeduh Kopi in Wongaya Gede Village. The study used a qualitative approach with interviews, observations, documentation, and questionnaires to strengthen data and address the identified issues. The results show that business development is supported by natural attractions, local community involvement, and digital promotion, while the main obstacles lie in facilities and access. The implementation of green practices is evident in waste sorting, the use of local food ingredients, and support for village cleanliness activities. These findings confirm that rural culinary businesses can contribute to sustainable tourism through consistent, simple innovations.